PENGEMBANGAN INSTRUMEN PENILAIAN PRAKTIKUM GENETIKA PADA SISWA SEKOLAH MENENGAH PERTAMA (SMP) - Yulinda Asnita (Jurnal Evaluasi Pendidikan, 2016)
The objective of the study is to develop the assessment instrument for genetic practicum for junior high school students. The sample of the study is computed by using proportionate stratified random sampling method. Conceptually, the construction of genetic practicum measures the three dimensions of abilities: cognitive, psychomotor, and affective. According to the experts and panelists, the results of the assessment items show that there are 51 items which are valid and with interrater of over 0.7 both for the exact indicators and the use of the language. In the first and second steps, the instruments have been tried out to 255 9th grade students. The result of the empiric test in the first and the second steps based on the analysis test for confirmation factors shows that some indicators have loading factor of over 0.5 with T- score of > 1,96. According to the computation of multi dimension for reliability coefficient in the first and second try outs, the score of the construction for reliability coefficient is more than 0.9 and the score of Average Variance Extracted (AVE) is above 0.4 which means that it proves the high level of the validity and reliability of the assessment instruments of genetic practicum for the Junior High School students.